2016
DOI: 10.1016/j.canlet.2016.02.032
|View full text |Cite|
|
Sign up to set email alerts
|

Helicobacter pylori upregulates Nanog and Oct4 via Wnt/β-catenin signaling pathway to promote cancer stem cell-like properties in human gastric cancer

Abstract: Helicobacter pylori (H. pylori) infection is considered a major risk factor for gastric cancer. CagA behaves as a major bacterial oncoprotein playing a key role in H. pylori-induced tumorigenesis. Cancer stem cells (CSCs) are believed to possess the ability to initiate tumorigenesis and promote progression. Although studies have suggested that cancer cells can exhibit CSC-like properties in the tumor microenvironment, it remains unclear whether H. pylori infection could induce the emergence of CSC-like propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
97
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(100 citation statements)
references
References 51 publications
3
97
0
Order By: Relevance
“…KRAS-mutation-specific T cells, as well as personalized mutation-specific T cells, have been identified, and these may be useful in the future for individual cancer immunotherapeutics[47]. It has been reported that Helicobacter pylori up-regulates Nanog and Oct4 expression via Wnt/β-catenin signaling[48]. Wnt/β-catenin signaling and the phosphorylation of β-catenin may be involved in stemness in gastric cancer[48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…KRAS-mutation-specific T cells, as well as personalized mutation-specific T cells, have been identified, and these may be useful in the future for individual cancer immunotherapeutics[47]. It has been reported that Helicobacter pylori up-regulates Nanog and Oct4 expression via Wnt/β-catenin signaling[48]. Wnt/β-catenin signaling and the phosphorylation of β-catenin may be involved in stemness in gastric cancer[48].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Helicobacter pylori up-regulates Nanog and Oct4 expression via Wnt/β-catenin signaling[48]. Wnt/β-catenin signaling and the phosphorylation of β-catenin may be involved in stemness in gastric cancer[48]. …”
Section: Discussionmentioning
confidence: 99%
“…It appears that the CagA/E-cadherin complex impairs the interaction between E-cadherin and pro-oncogenic β-catenin, resulting in the cytoplasmic and nuclear accumulation of β-catenin (Figure 1E). Nuclear accumulation of β-catenin is also increased in biopsies from patients with early and late gastric carcinoma [110,111] and in the gastric epithelium of Mongolian gerbils infected with the highly cancerogenic H. pylori strain 7.13 [112]. In MKN28 and MKN45 human gastric epithelial cells, transfected CagA deregulated β-catenin and then transactivated T-cell factor/lymphoid enhancer factor (TCF/LEF) and CDX1 transcription factor to induce the expression of cancer-associated Wnt target genes, such as c-myc and cyclin d1 [108].…”
Section: Caga Targets E-cadherin and Deregulates Catenin Signalingmentioning
confidence: 99%
“…Aberrant activation of Wnt signaling may contribute to numerous malignancies, such as colon cancer[6,7], gastric cancer[8], esophageal cancer[9], HCC[10], and others. Approximately 95% of observed HCC cases showed deregulation of the Wnt signaling cascade[11].…”
Section: Introductionmentioning
confidence: 99%